2017
DOI: 10.1186/s13023-017-0664-7
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing propranolol as a drug for the treatment of retinal haemangioblastomas in von Hippel-Lindau disease

Abstract: BackgroundVon Hippel-Lindau (VHL) disease is a rare oncological disease with an incidence of 1:36,000, and is characterized by the growth of different types of tumours. Haemangioblastomas in the central nervous system (CNS) and retina, renal carcinoma and pheochromocytomas are the most common tumours. The absence of treatment for VHL leads to the need of repeated surgeries as the only option for these patients. Targeting VHL-derived tumours with drugs with reduced side effects is urgent to avoid repeated CNS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…In summary, the results of Figs 6 and 7 demonstrate that Propranolol and ICI, both β2-blockers are preventing in some way the translocation of HIF-1α to nuclei which may explain the decrease of gene expression of HIF-targets shown in Fig. 5 and was previously shown in Albiñana et al, 2015/2017 19,21 .…”
Section: Ici-118551 Is An Antiangiogenic Agent Acting By Inhibiting supporting
confidence: 71%
See 3 more Smart Citations
“…In summary, the results of Figs 6 and 7 demonstrate that Propranolol and ICI, both β2-blockers are preventing in some way the translocation of HIF-1α to nuclei which may explain the decrease of gene expression of HIF-targets shown in Fig. 5 and was previously shown in Albiñana et al, 2015/2017 19,21 .…”
Section: Ici-118551 Is An Antiangiogenic Agent Acting By Inhibiting supporting
confidence: 71%
“…In this scenario, where surgery and pharmacological therapies show limited recovery and response for CNS VHL disease, an urgent requirement for new and more effective drugs with reduced side effects for these patients are demanded. www.nature.com/scientificreports www.nature.com/scientificreports/ Some previous studies from Shepard et al and our group have demonstrated that Propranolol, a non-specific β1-and β2-blocker, was efficient on in vitro treatment of CNS Hemangioblastomas primary cultures 19,21,52 . Basically, Propranolol was acting in two ways: i) decreasing cell viability by triggering apoptosis and ii) inhibiting the expression of HIF-dependent targets in VHL HB cells, where HIF-1α degradation is impaired 21 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Plasma VEGF levels have recently been reported to serve as a biomarker in patients with VHL disease taking propranolol for ocular VHL. 1 In a recent study, patients with VHL disease who harbored retinal hemangioblastomas received propranolol up to 120 mg/day. Although no retinal HBs regressed in the study, systemic VEGF levels decreased with prolonged treatment with propranolol, which is consistent with our in vivo findings.…”
Section: Discussionmentioning
confidence: 99%